IMPLEMENTASI KEBIJAKAN PENGELOLAAN HUTAN PADA TINGKAT TAPAK - Hanosoan Daulay; Sujianto Sujianto; Rahima Erna (JIANA ( Jurnal Ilmu Administrasi Negara ), 2018)
Implementation of Forest Management Policy at Site Level. This study aims to find out how the implementation of forest management policies at the level of site in Production Forest Management Unit (KPHP) Unit Unit XVIII Kampar Kiridan what factors become obstacles facing toward actual condition as an independent KPH. Informant research is the people who are considered to know things related to research problems. This research is included in case study research. The method used in this research is qualitative descriptive, data collection by interview, observation and studying regulation. The results show that the implementation of forest management policy at the site level in KPHP Unit Model XVII Kampar Kiri not in accordance with the policy which narrated in the form of regulation which have been issued by Ministry of Environment and Forestry (LHK) and still not fully get support from Local Government of Kampar Regency. The activities undertaken in KPHP Unit Model XVII Kampar Kiri have not entirely refer to the Long Term Management Plan (RPJP) for 10 years (2015-2024).